2011
DOI: 10.1186/1476-4598-10-68
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase turnover and recovery in sulforaphane-treated colon cancer cells: competing actions of 14-3-3 and Pin1 in HDAC3/SMRT corepressor complex dissociation/reassembly

Abstract: BackgroundHistone deacetylase (HDAC) inhibitors are currently undergoing clinical evaluation as anti-cancer agents. Dietary constituents share certain properties of HDAC inhibitor drugs, including the ability to induce global histone acetylation, turn-on epigenetically-silenced genes, and trigger cell cycle arrest, apoptosis, or differentiation in cancer cells. One such example is sulforaphane (SFN), an isothiocyanate derived from the glucosinolate precursor glucoraphanin, which is abundant in broccoli. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
114
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 66 publications
12
114
1
1
Order By: Relevance
“…Although histone deacetylase inhibitors are useful in the treatment of these cancers, they are associated with nonspecific effects. It has been reported that treatment with histone deacetylase inhibitors can induce concomitant degradation of HDAC3 and corepressors in cancer cells (48), confirming the inverse correlation between HDAC3 clearance and corepressor expression as observed here. Along with the presently observed HDAC3 reduction upon corepressor depletion in all cancer cell lines tested here, these studies suggest that the pathways driving HDAC3 degradation in tumors are intact.…”
Section: Discussionsupporting
confidence: 76%
“…Although histone deacetylase inhibitors are useful in the treatment of these cancers, they are associated with nonspecific effects. It has been reported that treatment with histone deacetylase inhibitors can induce concomitant degradation of HDAC3 and corepressors in cancer cells (48), confirming the inverse correlation between HDAC3 clearance and corepressor expression as observed here. Along with the presently observed HDAC3 reduction upon corepressor depletion in all cancer cell lines tested here, these studies suggest that the pathways driving HDAC3 degradation in tumors are intact.…”
Section: Discussionsupporting
confidence: 76%
“…Its chemopreventive effects have assigned to multiple mechanisms such as modulatory action on phase 2 enzymes via Keap1-Nrf2 signaling and antioxidant response element (ARE)-driven gene expression as well as by induction of cell cycle arrest and apoptosis and inhibition of histone deacetylase (HDAC) (Clarke el al., 2011;Rajendran et al, 2011). Conspicuously, SFN has been shown to selectively target the precancerous and cancerous cells (Clarke el al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies involved in the evaluation of sulforaphane as an HDAC inhibitor, and those aimed at providing insights into the mechanisms associated with sulforaphane-regulated inhibition of HDAC activity, have focused on the roles of HDAC3 and HDAC6 as important targets (43, 89,223,224). After the incubation of HCT116 human colon cancer cells with 15 lM sulforaphane, a significant reduction in HDAC1, HDAC2, HDAC3, and HDAC8 was observed compared with vehicle-treated cells at 36 h post administration (223).…”
mentioning
confidence: 99%